Interactions of Ricoseius loxocheles (Acari: Phytoseiidae) and coffee leaf rust - OLIVEIRA, Cléber Macedo de (2012)
Coffee crops have aconomic losses die pests and diseases Among them, the phytophagous wwits deserve atention che to the mhicing photosynthetic area caused on the leaves. Besikes of mite damages, some pathogens also attack coffee plants, as the coffee rust tangus, Nemileie wastatrh (thedinales). This pathogen cause yield losses around 30% in soNIne vaniehes of Cen arabica. Pretatory mites from the Phytoseiidae family nomally conhol phytphaous mites and can develop and reprohice using various altemative food sONrces than their primary prey, ten anychid mites. Within the Phytoseiidae family that is composed by carmivorous and pollen-feeding mites, ne surveyed in the field the species Rcesahs lovacheles (De Leon) (Acari: Phytoseiidae) on the necrosis area caused by coffee ust daning is reprodactive phase Searching in the hiteratre showed that there is httle infematon related to this mite development, biological parameters and feeding habits. So, this shaty was camed out to assess the taxonomy, development, survivorship and reprodaction paraneters of R. doacheles feeding on coffee nust fungus, its predation capacity on Olgopols aets (MoGregor, 1971) and its reproductive success. Coffee rust supported the suvaval development and reproduction of the phytoseiid mite and that it was aot able to ed on different stages of O cis Survival and oviposition of R lexocolelies was only observed when this nute was in arenas mith fungi In arenas without fingi these parameters were equal as arenas without food t is known that reproduction has a higher wmhonal requirement than development The fertihity of R lovocheles fed on coffee rust is huphest that the other phytoseud fed in others fungt or some mites or pollen We suggest that this mute as a phytoseid generaist and it is necessary more shadies to measture the o ssad soms aet te ns samos poY ANDO O pooy s t sup o e coffee crops h is possible that R loacheles has a role in the control of coffee rust sance it Reeds on a lrge amount of rust ueedospore.